1999
DOI: 10.1063/1.125375
|View full text |Cite
|
Sign up to set email alerts
|

Formation of silicon–oxide layers at the interface between tantalum oxide and silicon substrate

Abstract: Silicon–oxide layers formed at the tantalum–oxide/silicon interface were investigated by using Fourier transform infrared spectroscopy (FTIR). The samples were annealed in oxygen atmosphere, in nitrogen atmosphere, and in vacuum. It has been found that the formation of the interfacial silicon–oxide layers depends neither on the tantalum–oxide thickness nor on the annealing atmosphere, but on the annealing temperature. The silicon–oxide layer is formed even by annealing in vacuum. It is concluded that the silic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(6 citation statements)
references
References 11 publications
1
5
0
Order By: Relevance
“…The discrepancies that were sometimes observed during the first one or two oxidation–reduction cycles correspond to irreversible stress changes, perhaps due to small variations in the microstructure of the film or to the formation of an oxide layer at the substrate–film interface and at the back of the Si substrate. For example, work done by Ono and Koyanagi 15 with Ta 2 O 5 films on Si showed the formation of a stable interfacial silicon‐oxide layer that depends neither on the Ta 2 O 5 thickness nor on the annealing atmosphere. Similar behavior for TiO 2 films deposited on Si has been observed where the formation of a stable Si–O–Ti interfacial layer is reported to be in the range of 5–10 nm 16,17 .…”
Section: Resultsmentioning
confidence: 99%
“…The discrepancies that were sometimes observed during the first one or two oxidation–reduction cycles correspond to irreversible stress changes, perhaps due to small variations in the microstructure of the film or to the formation of an oxide layer at the substrate–film interface and at the back of the Si substrate. For example, work done by Ono and Koyanagi 15 with Ta 2 O 5 films on Si showed the formation of a stable interfacial silicon‐oxide layer that depends neither on the Ta 2 O 5 thickness nor on the annealing atmosphere. Similar behavior for TiO 2 films deposited on Si has been observed where the formation of a stable Si–O–Ti interfacial layer is reported to be in the range of 5–10 nm 16,17 .…”
Section: Resultsmentioning
confidence: 99%
“…17 it is shown that IR methods have also been used to study composition and thickness of SiO x films at the interface of Ta 2 O 5 and other oxide films deposited on Si, and the evolution of such layers upon thermal treatment. 103,107…”
Section: A Optical Methodsmentioning
confidence: 99%
“…Another factor that has to be taken into account for the NH 3 -nitrided systems is the undoubted presence of hydrogen species in the structures-NH 3 treatment unlike the N 2 O one is supposed to result in hydrogen incorporation into the film. (Virtually the hydrogen incorporation is an attribute of the NH 3 nitridation process [25].) The amount of hydrogen is expected to rise with increasing T n .…”
Section: C-v Characteristicsmentioning
confidence: 99%
“…The incorporation of nitrogen into the Si/Ta 2 O 5 interface could prevent the formation of a silicide layer during Ta 2 O 5 deposition and relax the compressive interface stress to strengthen the interface. The techniques mostly employed to perform the nitridiation of Si wafers are rapid thermal and plasma processing in ammonia, nitrous oxide and nitric oxide and chemical vapour deposition [15][16][17][18][19][20][21][22][23][24][25]. Introduction of a thin (0.5 nm) TaN x layer which is transformed to TaO x N y after Ta 2 O 5 deposition and high temperature annealing was also suggested in order to improve the dielectric and electrical properties of the stacks [26].…”
Section: Introductionmentioning
confidence: 99%